Prevalence of metabolically-obese normal-weight worldwide: systematic review and meta-analysis - Vera Ponce, Víctor Juan (2023)
Background: Obesity causes the loss of body homeostasis and pre-disposes to the development of disease; some individuals present al-terations described even having a normal body mass index (BMI), and these are called thin metabolically obese. The objective was to carry out a systematic review with meta-analysis to determine the preva-lence of metabolically-obese normal-weight (MONW) worldwide.Methods: The search for studies was conducted from May to June 2022 in the EMBASE, PubMed, WOS, and Scopus databases. The pu-rification and ordering of data were carried out using the Excel 2016 program, later a meta-analysis with the Stata version 17 program.Results: A total of 408,251 people with normal BMI were identi-fied, of whom 78,054 had a metabolic disorder, and the prevalence after the meta-analysis was 26.78% (95% confidence interval: 18.45 - 36.03) with high heterogeneity (I2 = 99.86%).Conclusion: The findings of the systematic review confirm a high prevalence of MONW worldwide.